PENGEMBANGAN MEDIA PEMBELAJARAN RAMA BERBASIS KINEMASTER PADA MATA PELAJARAN IPA KELAS IV SEKOLAH DASAR - Al darmono darmono; Dhian Dwi Nur Wenda Wenda (Kurikula : Jurnal Pendidikan, 2022)
ABSTRACT The lack of students' understanding of the food chain material that causes low student learning outcomes this occurs because the learning activities carried out by teachers are still oriented to conventional learning activities. The purpose of this study was to develop Kinemaster-based RAMA learning media. This research method is an R&D (Research and Development) research with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. For data collection, descriptive analysis was used for observation and interview data, while statistical analysis was used for data resulting from validation, practicality and effectiveness in the form of numbers. For media expert validation, a score of 91.87% was obtained with a very valid category, and material experts got a score of 94.37% in a very valid category, the results of product practicality by practitioners obtained a score of 87.5% in a very practical category and for student responses a score was obtained. 96.25% with a very practical category, then the effectiveness data seen from the results of the pre-test and post-test obtained 67.5% before and 81.25% after using the media. Based on these data, there was a significant increase in the pre-test and post-test scores.